Implementasi Layanan Bimbingan Konseling di SMP Al-Madina Wonosobo - Kamila Fithrachatun Nisa; Sri Haryanto; Salis Irvan Fuadi (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
Education is the main foundation in shaping the character and personality of the younger generation. Every educational institution has a responsibility to not only convey knowledge, but also guide its students in emotional and social aspects. In this context, guidance and counseling services play an important role in helping students overcome the various challenges they face, both in the school environment and outside of school. This research aims to explore how the implementation of guidance and counseling services at Al-Madina Middle School Wonosobo works, as well as its impact on student development. This research uses a qualitative descriptive method with data collection techniques through interviews, observation and documentation studies. The research results show that Al-Madina Middle School Wonosobo has implemented various structured and comprehensive counseling guidance programs. These programs include academic guidance, personal guidance, and social guidance. Implementation of this service has been proven to help students increase learning motivation, overcome personal problems, improve social interactions, and plan their future.